Effect of welding on distortion changes in fillet joints with different sequences - Cuana, Rona; Purba, Adi Syahputra; Putra, Gelby Anggara; Muvariz, Mufti Fathona; Amalia, Mutia (International Journal of Mechanical Computational and Manufacturing Research, 2025)
Gas Metal Arc Welding (GMAW) is widely used in fabrication due to its efficiency and weld quality. This study examined the influence of welding sequence on distortion in 316 stainless steel fillet joints using the GMAW-pulsed process. Two techniques—back-step welding and string welding—were applied without strongbacks on 50 mm × 50 mm × 5 mm specimens, with 3–5 seconds between passes. Distortion was measured using a trigonometric calculation based on displacement. Results show that back-step welding consistently reduced angular distortion compared to string welding. For vertical plates, back-step yielded 14.53°, 13.59°, and 14.30°, versus 15.42°, 14.07°, and 14.76° for string welding. For horizontal plates, values were –3.93 mm, 4.12 mm, and –6.20 mm for back-step, compared to –10.15 mm, 1.91 mm, and –8.20 mm for string welding. Reduced distortion is attributed to intermittent bead placement, which limits heat accumulation and residual stress. These findings highlight the importance of sequence selection in minimizing distortion, particularly in precision-demanding sectors such as marine and automotive fabrication, and support the inclusion of back-step welding in welder training programs.